Students' perceived factors of learning computer science education through a social networking site - Yusop, Junaidah (2015)
Despite the increasing popularity of social networking sites (SNS) due to a major involvement of students in online social activities, there is a significant challenge involved in using SNS, particularly as a learning platform in teaching computer science education (CSE) to undergraduate students in non-engineering and engineering studies. To find out the perceived factors of learning through SNS approaches, questionnaires were distributed to a total of 219 undergraduate students ranging from non-engineering (n=80) to engineering (n=139). From the questionnaire, five constructs were identified as: sharing perspective, communicative process, cohesiveness expression, peer interaction, and tools and resources. The evaluation of students’ learning transcripts in SNS indicated teaching CSE through SNS enhanced students’ understanding of CSE. The study is shown to support social constructivism, which promotes knowledge that is distributed across a network of connections.